Adsorption mechanism of arsenic ion on iron modified montmorillonite - Dela Cruz, Michael Leo L. (Quezon City College of Engineering, University of the Philippines Diliman, 2011)
With the thought of obtaining a large surface area with increased capacity for adsorption in nanoparticles, iron-modified montmorillonite (Fe-MMT) was synthesized through ion exchange where Na⁺ in sodium montmorillonite (Na-MMT) was replaced with Fe³⁺ to produce Fe-MMT. Subsequent reduction of Fe-MMT was done to reduce the Fe³⁺ to Fe0 and produce zero-valent iron-MMT (ZVI-MMT). The iron and sodium content on both iron-modified nanoclays were quantified through inductively coupled plasma mass spectrometry (ICP-MS) analysis where a significant increase in iron was measured with consequent decrease in sodium content. Surface morphology analysis of the modified nanoclays using scanning electron microscope (SEM) showed flakey morphology which is a characteristics of MMT. Transmission electron microscope (TEM) micrographs of ZVI-MMT. Moreover, x-ray diffraction (XRD) pattern of both adsorbents confirm, the presence of MMT as well as presence of iron compounds. Batch adsorption technoque was employed in determining the adsorption efficiency of both adsorbents. A 2³ factorial design was used in identifying significant factors, wherein effects of pH, initial concentration and adsorbent type were studied where it was found that ZVI-MMT has a wider range of applicability, i.e. pH 4-11, and could have a removal efficiency as high as about ~100%. Equilibrium data of Fe-MMT and ZVI-MMT fitted well to langmuir model with monolayer capacities of 10.13 and 20.12 mg/g, respectively. Kinetics data of Fe-MMT had a good fit to intra-particlediffusion and pseudo-second order reaction models. ZVI-MMT was found to be solely adsorption reaction controlled due to its good fit to pseudo-second order reaction model.
Thesis (M.S. Materials Science and Engineering)--University of the Philippines, Diliman.
Keywords: Iron -- Absorption and adsorption; Ion exchange; Iron modified montmorillonite